2011
DOI: 10.1007/s00125-011-2162-0
|View full text |Cite
|
Sign up to set email alerts
|

No evidence of an increased mortality risk associated with low levels of glycated haemoglobin in a non-diabetic UK population

Abstract: Aims/hypothesis There is debate about increased mortality risk associated with low levels of glycaemia. To address this issue, we examined the shape of the risk relationship between glycated haemoglobin and mortality in a UK population. 16-1.80]). Spline regression suggested no increased risk at the low end of the distribution. Indeed, the HR for all-cause mortality was virtually constant in the low range and only started to rise when the level was approximately 5.5%. There were similar associations of glycat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
43
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 28 publications
(31 reference statements)
2
43
2
Order By: Relevance
“…Selvin et al [22], supported by results from Carson et al [23], found a J-shaped association between HbA 1c level and all-cause mortality, with lowest mortality for people (without diabetes) with an HbA 1c level between 5.0% and 5.5% (31 and 37 mmol/mol). A recent large study [24] found no evidence of such a J-shaped association, but rather a monotone relationship, with lowest risk for lowest HbA 1c . We found a trend towards a J shape, with lowest mortality for HbA 1c levels between 6.0% and 6.9% (42 and 52 mmol/mol).…”
Section: Discussionmentioning
confidence: 91%
“…Selvin et al [22], supported by results from Carson et al [23], found a J-shaped association between HbA 1c level and all-cause mortality, with lowest mortality for people (without diabetes) with an HbA 1c level between 5.0% and 5.5% (31 and 37 mmol/mol). A recent large study [24] found no evidence of such a J-shaped association, but rather a monotone relationship, with lowest risk for lowest HbA 1c . We found a trend towards a J shape, with lowest mortality for HbA 1c levels between 6.0% and 6.9% (42 and 52 mmol/mol).…”
Section: Discussionmentioning
confidence: 91%
“…Moreover, a number of studies have analyzed the relationship between HbA 1c and all-cause mortality. Most of these previous studies observed an increased risk of death from all-causes at diabetic HbA 1c levels among adults without known diabetes, independent of other known cardiovascular risk factors (6)(7)(8)(9)(10)(11), whereas some studies found no significant association (12)(13)(14). Whether the risk for all-cause mortality is already increased at HbA 1c levels in the prediabetic range is unclear.…”
mentioning
confidence: 77%
“…Whether the risk for all-cause mortality is already increased at HbA 1c levels in the prediabetic range is unclear. Former studies showed contradictory results and differed in applied HbA 1c cutoffs (6,(9)(10)(11)(12)(13)(15)(16)(17). So far, only one previous study assessing all-cause mortality in relation to HbA 1c in the prediabetic range applied ADA recommendations.…”
mentioning
confidence: 99%
“…Interestingly, the recent literature is quite inconsistent about the relationship between the effect of low HbA 1c and the risk of mortality or CVD [15]. Various studies demonstrated a consistent positive linear relationship between HbA 1c and the risk of mortality or CVD [29,30]. Other studies revealed a non-linear (U-or J-shaped) relationship [31,32].…”
Section: Discussionmentioning
confidence: 99%